The Influence of Entrepreneurial Characteristics on the Entrepreneurial Interest of Management Students at Universitas Mitra Bangsa Jakarta - Anindya Nurani Mutiara Sari; Eny Ariyanto (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The development of Indonesia’s creative economy requires the availability of young human resources who possess strong entrepreneurial characteristics. Universities are expected to play a vital role in fostering entrepreneurial interest among students, particularly those in management programs. This study aims to analyze the influence of entrepreneurial characteristics, including entrepreneurial self-efficacy (ESE), innovation, risk-taking, proactiveness, and resilience, on the entrepreneurial interest of management students at Universitas Mitra Bangsa (UMIBA) Jakarta. The research employs a quantitative, survey-based approach. Data were collected through a structured questionnaire measured on a five-point Likert scale and distributed to 62 active management students from the 2023 cohort and earlier. Multiple linear regression analysis was used to examine the simultaneous and partial effects of the independent variables on entrepreneurial interest. The results indicate that entrepreneurial characteristics simultaneously have a significant effect on entrepreneurial interest (F = 3.159; Sig. = 0.014), with a coefficient of determination (R²) of 0.220. This suggests that 22% of the variation in entrepreneurial interest can be explained by the entrepreneurial characteristics examined in this study. Innovation shows the strongest positive, statistically significant influence, while entrepreneurial self-efficacy, risk-taking, proactiveness, and resilience exhibit positive but statistically insignificant effects. These findings emphasize the importance of strengthening innovation-oriented learning and experiential entrepreneurship programs in higher education to enhance students’ entrepreneurial interest.